Analisis Strategi Komunikasi Krisis Klinik Kesehatan Gigi di Masa Pandemi COVID-19 - Salsabilla Arum Puspitasari; Subhan Afifi (Program Studi Ilmu Komunikasi UII, 2022)
The dental health clinic is one of the institutions experiencing a crisis during the COVID-19 Pandemic. People who are worried about contracting COVID-19 refrain from visiting various health service institutions, including the Dental Health Clinic, which is considered a source of transmission because it is related to the mouth and teeth. This has an impact on decreasing the number of patients and affecting the existence of the business. This study aims to analyze the crisis communication strategy of a Dental Health Clinic in Banjarmasin during the COVID-19 Pandemic. The method used in this research is the case study method as part of descriptive qualitative research. Data collection techniques used in-depth interviews, observation and document analysis. The results showed that although the Dental Health Clinic, which was the object of the study, did not have a special Public Relations, it had carried out the role and function of Public Relations in crisis communication. The crisis communication strategy is implemented in a planned and systematic manner in 3 crisis phases: Pre-crisis, crisis and Post-crisis. Clinic Management Accommodative Strategy with Rectification as a crisis communication strategy tactic during the COVID-19 Pandemic. The use of direct communication demonstrates this through the spokesperson and optimization of the use of social media to convey information and education to the public. This research provides academic and practical contributions related to Crisis Communication Strategies in the world of health and enriches the scientific treasures of Health Communication in Indonesia.